2019
DOI: 10.32598/jhnm.29.4.236
|View full text |Cite
|
Sign up to set email alerts
|

Nurses’ Knowledge of Palliative Care and Its Related Factors

Abstract: Palliative care is the science of promoting the patient's quality of life. It can improve the quality of life of a patient, which is effective not only in patient's late-life but also useful in dealing with a chronic illness over many years. In this regard, nurses, as the largest providers of health care services, play an important role in palliative care.Objective: This study aimed to investigate the palliative care knowledge of nurses and its contributing factors. Materials and Methods:This cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(39 citation statements)
references
References 19 publications
8
27
0
Order By: Relevance
“…Having a bachelor of science or a higher degree in nursing, working in an emergency department, having a daily experience of caring for chronically ill patients, and taking part in a training on the end-of-life care were significantly associated with good knowledge of nurses toward the end-of-life care [ 28 ]. Nurses with a poor understanding of palliative care were the main limitation to providing excellent palliative care [ 3 ]. The level of knowledge of nurses as well as experience in advance directives (ADs) discussions reported a moderate level of confidence to explain ADs to patients and their families [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Having a bachelor of science or a higher degree in nursing, working in an emergency department, having a daily experience of caring for chronically ill patients, and taking part in a training on the end-of-life care were significantly associated with good knowledge of nurses toward the end-of-life care [ 28 ]. Nurses with a poor understanding of palliative care were the main limitation to providing excellent palliative care [ 3 ]. The level of knowledge of nurses as well as experience in advance directives (ADs) discussions reported a moderate level of confidence to explain ADs to patients and their families [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that providing DNR information to the patient was important, but a few nurses and physicians stated that they often discuss DNR with patients before issuance [ 2 ]. The better the nursing staff’s knowledge and attitude toward the terminal patients’ care, the more confident they can be in discussing DNR and hospice care with terminal patients and their families [ 3 ]. DNR discussion should be carried out as early as possible when the patient is relatively healthy and is still able to understand its undertakings, as well as provide a reference for the terminal patient and family members to make medical decisions to provide better care [ 2 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Having a bachelor of science or a higher degree in nursing, working in an Emergency department, having a daily experience of caring for chronically ill patients and taking part in a training on end of life care were signi cantly associated with good knowledge of nurses toward the end of life care [21]. Nurses with poor knowledge of palliative care were the main limitation to providing good palliative care [3]. The level of knowledge of nurses as well as experience in advance directives (ADs) discussions reported a moderate level of con dence to explain ADs to patients and their families [22].…”
Section: Factors Affecting the Kap-dnr Among Nursesmentioning
confidence: 99%
“…The level of knowledge of nurses as well as experience in advance directives (ADs) discussions reported a moderate level of con dence to explain ADs to patients and their families [22]. Nurses can improve their knowledge through in-service education and on job retraining to promote the quality of palliative care services for the patients [3]. Therefore, it is crucial to participate in the DNR signature with patients or family and receive education related to palliative care to improve the nurses' knowledge toward DNR.…”
Section: Factors Affecting the Kap-dnr Among Nursesmentioning
confidence: 99%
See 1 more Smart Citation